On the computation of some homological functors of 2-engel groups of order at most 16 - Hazzirah Izzati Mat Hassim; Nor Haniza Sarmin; Nor Muhainiah Mohd Ali; Mohd Sham Mohamad (Penerbit Universiti Kebangsaan Malaysia, 2011)
The homological functors including J (G) , ∇(G) , exterior square, the Schur multiplier, Δ(G) , the symmetric square and J